Vom gläsernen Sarg zum «Glaspalast des Männlichen». Volksmärchen und feministische Philosophiekritik in Elfriede Jelineks Schneewittchen-Adaption «Der Tod und das Mädchen I» (Studia austriaca, 2014)
Elfriede Jelineks postdramatic drama Death and the Maiden I represents a feminist revision of the fairy tale Snow White by the Brothers Grimm. Jelinek applies the ideologically and patriarchally loaded medium “fairy tale” to develop a highly differentiated feminist criticism on Western philosophy. Thus, this adaption has to be put in the context of the pre-existing intertext by Brothers Grimm, feminist literary criticism and deconstruction. This essay examines where and how Jelinek instrumentalizes and modifies popular fairy tale motifs in order to create a multi-layered criticism of ontological gender paradigms, patriarchal structures in philosphical thinking, and ideals of beauty.